The Impact of Christianity on the Extinction of Ekau Feminine Cult in Ekori - John, Sunday Edet; Eteng, Nzeyo Gabriel (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
There is no argument that Christianity played a great and positive role in Ekori by getting rid of heinous cultural practices, provision of health care services and educating the people, but it has also robbed the people of certain cultural institutions and heritage. Ekau Cult was a highly placed and important social institution that played a variety of roles in the community; ranging from maintaining ethical order and stability, judicial, economic and security roles. The qualitative method of data collection and analysis which includes both primary and secondary materials. Primary data were gathered from the field through extensive oral interviews under a conducive atmosphere void of external influences which attest to the originality of the information obtained. The secondary data includes works written by scholars found in journals, textbooks and Internet. It was discovered in the course of this research that the extinction of Ekau Feminine Cult has resulted to insecurity, moral decadence, infertility and infidelity, broken relationships, domestic violence, among others. The need for cultural revivalism, self identity and religious tolerance is among the recommendations made in this work.